Penyuluhan Pola Makan Sehat Pada Ibu Hamil Di Kabupaten Bulukumba: Penyuluhan Pola Makan Sehat Pada Ibu Hamil Di Kabupaten Bulukumba - Nursyahraeni Madika Rahman; Isnaeni Isnaeni; Rika rika (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
Maternal nutritional status before and during pregnancy can affect the growth of the fetus being conceived. Pregnant women need adequate nutrition for the health of the mother and fetus. Nutrition education is a field of knowledge that enables a person to choose and maintain a diet based on nutritional science principles. This service activity was carried out on March 3, 2023 at the Taccorong Village Office, Kec. Ujung Bulu, Kab. Takalar. The method used is by giving lectures, demonstrating the presentation of healthy eating patterns during pregnancy, discussions, and gathering feedback. The results of this service show that pregnant women understand healthy eating patterns as evidenced by the participants being able to answer all questions correctly. of course this will be easier to realize if pregnant women understand the concept. One way to get a good concept is by providing health counseling/education. Providing good health education will make it easier for pregnant women to adopt knowledge about their health so that they are able to deal with nutritional and family health problems and through education about healthy eating patterns during pregnancy is very important to convey to pregnant women because along with the development of information and communication technology , pregnant women are expected to be able to know about diet which consists of the type of food, amount of food and schedule. Keywords: Pregnant Women, Healthy Eating Patterns, Counseling